The History of Science in a World of Readers - Angela N. H. Creager (Studies 11: Max Planck Research Library for the History and Development of Knowledge, 2020)
What role should historians of science, technology, and medicine have in communicating their own body of literature-its methods and concerns-across linguistic boundaries? This anthology is a proactive response to this question. As the West and the East become ever more closely related through travel, trade, and-not least-the globalization of knowledge, the seven essays in this volume should stimulate new engagements between English and Chinese readers on the centrality of science, technology, and medicine for our histories and our future. A wider selection of influential literature published in English since 1990 has been translated into Chinese and published in China in a companion volume. The series Studies of the Max Planck Research Library for the History and Development of Knowledge is dedicated to key subjects in the history and development of knowledge, bringing together perspectives from different fields and combining source-based empirical research with theoretically guided approaches. Studies typically present working group volumes with integrative approaches. The volumes are available both as print-on-demand books and as open-access publications on the Internet. The material is freely accessible online at www.edition-open-access.de.